Vaccination Is Associated With Shorter Time to Target Cycle Threshold Value in Patients With SARS-CoV-2 Omicron Variant - Wu, Jiajun; Wei, Yong; Shen, Feng; Zhu, Shun; Lu, Yingying; Tian, Xue; Zhang, Pengyu (Frontiers in Cellular and Infection Microbiology, 2022)
Background Limited data are available on the responses to vaccination for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant in the Chinese population. This study aimed to investigate whether vaccination could alter the disease course of SARS-CoV-2 Omicron variant. Methods A retrospective cohort included 142 patients who had no or mild symptoms and were admitted to our department for centralized isolation after being locally infected with SARS-CoV-2 Omicron variant from March 4 to 30, 2022, in Shanghai, China. Results Of the 142 subjects with the mean age of 43.1 years, 53.5% were male and 90.8% had been vaccinated before the infection. Comparing the vaccinated with the unvaccinated patients, there was no difference in patient characteristics, but patients with vaccination had shorter time to target cycle threshold value (TtCT) (vaccinated vs. unvaccinated, 12.6 ± 3.4 vs. 14.8 ± 4.7 days, P = 0.039). There was no difference in TtCT between heterogeneous and homologous vaccination. Of subjects with homologous vaccination, 43.1% were vaccinated with CoronaVac (Sinovac Life Science), 47.2% with Sinopharm BBIBP-CorV, 4.9% with Sinopharm WIBP, 3.3% with CanSinoBio, and 1.6% with Zhifei Longcom. No difference in TtCT was observed among different vaccines. Comparing two-dose primary vaccination with three-dose booster vaccination, we found no difference in TtCT either. Conclusion Vaccination is associated with shorter TtCT in patients with SARS-CoV-2 Omicron variant.